Comparative Anatomy of the Neurocranium in Some Wild Carnivora - Atalar, Omer; Ustundag, Yasemin; Yaman, Mine; Ozdemir, Dervis (Medwell Online, 2009)
This study was carried out to investigate the specific anatomical features of the neurocranium in the lynx, wolf, fox and marten. Three from each species were used without sexual distinction. The dorsal surface of the neurocranium consisted of a paired parietal and frontal bones. Crista sagittalis externa was more significant in the wolf than in others species. Processus mastoideus was developed in all species examined. There were two foramen laterally on the each side of the Condylus occipitalis in the wolf These foramens were not seen in other species. Processus paracondylaris was projected caudally and slightly in the lynx. The frontal zygomatic process was slightly developed in the marten. The supraorbital foramen was absent in all species examined. Protuberentia occipitalis externa was seen as distinct structure in the fox and marten. The results of the present study may contribute to extension of data in this field of science.
Keywords: Anatomy; neurocranium; lynx; wolf; fox; marten